The Principle of Legality vs. Digital Sentencing Innovation: The Dialectics of Revocation of Internet Access Rights as a Criminal Penalty in Cybercrime Cases - Amirullah, Setyo; Sodikin, Sodikin (CV. Social Politic Genius (SIGn), 2025)
The evolution of increasingly sophisticated cybercrimes, such as revenge porn, has triggered a paradigmatic tension within the Indonesian criminal justice system between the need for sentencing innovation and absolute adherence to the principle of legality. This research aims to analyze disparities in legal paradigms across court levels, examine the juridical qualification of the penalty for the digital restriction order, and examine the constitutional implications of the cyber norm vacuum. Through prescriptive doctrinal legal research, this study dissects Decision Number 6069 K/Pid.Sus/2023, which affirms Decision Number 96/Pid.Sus/2023/PT BTN regarding the annulment of the additional penalty of revocation of internet access rights in Decision Number 71/Pid.Sus/2023/PN Pdl. The research results indicate that such annulment constitutes an affirmation of legal positivism, rejecting judicial activism, even though, sociologically, this penalty is crucial for preventing recidivism. Juridically, this penalty lacks a basis of legitimacy in the EIT Law, the Old Penal Code, or the New Penal Code, thereby creating a legal vacuum (rechtsvacuum) that harms victims. The research concludes that formal adherence to the principle of nullum crimen, nulla poena sine lege without accompanying legal reform has injured substantive justice. Therefore, it is recommended that legislators immediately undertake legislative modernization by adopting digital rights restriction penalties as a constitutional sentencing instrument to ensure the justice system’s responsiveness in tackling crime in the era of technological disruption.